Crime of rape of vulnerable: an analysis of police reports and investigations - RODRIGUES, Ariane Lilian Lima dos Santos Melo (International Journal of Development Research, 2023)
The present study has as objective to analyze police reports on crimes of rape of vulnerable, registered at police stations in the city of Belém – PA (Brazil), in order to evaluate the flux of conversion of police reports into investigations and the conversion of police investigations into court lawsuits, as well as identifying the demand of such crime. For such, the data used has been provided by the platforms of Secretaria Pública Adjunta do Estado do Pará (Assistant Public Secretary of State of Pará)(SIAQ/SISP) and the Tribunal de Justiça do Estado do Pará (Court of Justice of State of Pará), through the system of management of court lawsuits (LIBRA). The main focus was to demonstrate the number of incidence of this offense type, and at the same time, to ascertain, inside an universe of police reports how many are, indeed, investigated by the police unities, in other words, how many police reports are converted in police investigation. The results indicated that the number of occurrences registered was decreasing during the period analyzed.A concentration of 67,10% of the police reports was found in only 11 neighborhoods of Belém, from the 32 (thirty two) that make up the capital of Pará. Besides that, it was concluded that 92% (ninety two) of the reports registered were converted into Police Investigations.